On-surface transmetallation of metal–organic frameworks on Au(100) - Mischke, Valentin (Technische Universität Dortmund, 2026)
Metal–organic frameworks (MOFs) provide a modular strategy for engineering materials with targeted properties by combining metal nodes and organic linkers in a defined geometry. This thesis explores the on-surface assembly of MnTPyP on Au(100) into well-defined, reactive two-dimensional coordination networks. Deposition of Co or Ni, followed by mild annealing, converts the initial monolayer into an ordered, commensurate two-dimensional lattice. Structural and spectroscopic measurements show that the porphyrin macrocycle remains largely flat on the surface, while the pyridyl groups tilt out of the molecular plane. In addition, the data indicate on-surface transmetallation, i.e., replacement of Mn by Co in the macrocycle. Core level spectroscopy shows that two cobalt species coexist in the final network, consistent with Co(II) in the macrocycle and a Co(I) state at the pyridyl coordination nodes. Across multiple core levels, network formation induces an almost rigid binding energy shift, indicating modified interface energetics rather than only local bonding changes. Momentum microscopy relates this to the valence electronic structure: ligand-derived states retain recognizable molecular fingerprints, while an additional low-binding-energy contribution develops with weak momentum selectivity, consistent with enhanced electronic coupling within the coordinated lattice. An analogous network is obtained after Ni deposition, with a geometry similar to that of the Co-based system. The Ni 2𝑝_3/2 spectra likewise reveal two chemically distinct components, assigned to Ni(I) nodes and Ni(II) incorporated into the macrocycle, supporting transmetallation also in the Ni case. Finally, the chemical functionality of the coordination nodes is probed by exposing both networks to NO2 and CO. In both systems, gas dosing suppresses the M(I) signature and shifts spectral weight toward higher oxidation states, identifying the +1 node species as the redox-active center, while the macrocycle-bound +2 species remains comparatively inert. Adsorption occurs at room temperature and is reversible upon mild annealing, demonstrating switchable, surface-confined redox chemistry at well-defined coordination nodes.

Metall–organische Netzwerke folgen einem Baukastenprinzip, mit dem sich Materialien mit gezielt einstellbaren Eigenschaften realisieren lassen. Dabei werden Metallzentren und organische Linker in einer wohldefinierten Geometrie kombiniert. Diese Arbeit untersucht die oberflächengestützte Synthese reaktiver zweidimensionaler Koordinationsnetzwerke aus MnTPyP auf Au(100). Durch Deposition von Co bzw. Ni und anschließendes mildes Tempern wird die Ausgangsmonolage in ein geordnetes, kommensurates zweidimensionales Netzwerk überführt. Strukturelle und spektroskopische Messungen zeigen, dass der Porphyrin-Makrozyklus auf der Oberfläche weitgehend flach bleibt, während die Pyridylgruppen aus der Molekülebene herausgedreht sind. Zugleich zeigen die Daten, eine Transmetallierung, die Ersetzung von Mn mit Co im Makrozyklus. Rumpfniveauspektren belegen darüber hinaus zwei koexistieren Cobalt-Spezies im Netzwerk, wobei Co(II) im Makrozyklus und Co(I) an den Pyridyl-Koordinationsknoten zugeordnet wird. Die Netzwerkbildung führt über mehrere Rumpfniveaus hinweg zu einer nahezu starren Bindungsenergieverschiebung, was auf eine Änderung der Grenzflächen-Energetik und nicht nur auf lokale Bindungseffekte hinweist. Impulsmikroskopie verknüpft dies mit der Valenzbandstruktur: charakteristische molekulare Fingerabdrücke bleiben erhalten, zugleich entsteht ein zusätzlicher niederbindungsenergetischer Beitrag mit schwacher Impulsselektivität, was auf eine stärkere elektronische Kopplung innerhalb des Netzwerks hindeutet. Ein entsprechendes Netzwerk lässt sich auch nach Ni-Deposition herstellen, mit einer Geometrie, die der des Co-basierten Systems weitgehend entspricht. Die Ni 2𝑝_3/2-Spektren zeigen ebenfalls zwei klar unterscheidbare Komponenten, die Ni(I)-Knoten sowie Ni(II) im Makrozyklus zugeordnet werden und damit auch für Ni eine Transmetallierung stützen. Abschließend wird die chemische Funktion der Koordinationsknoten durch Exposition gegenüber NO2 und CO untersucht. In beiden Netzwerken wird das M(I)-Signal durch Gasdosierung unterdrückt und Intensität zu höheren Oxidationsstufen verschoben. Damit wird die +1-Spezies an den Knoten als redox-aktives Zentrum identifiziert, während die +2-Spezies im Makrozyklus vergleichsweise unbeeinflusst bleibt. Die Adsorption erfolgt bei Raumtemperatur und lässt sich durch mildes Tempern rückgängig machen, was schaltbare, oberflächengebundene Redoxchemie an wohldefinierten Koordinationsknoten demonstriert.
Structure, electronic properties, and gas-induced reactivity
Keywords: MOF; XPS; XAS; LEED; MM; MnTPyP; Molecules; Cobalt; Nickel; CO; NO2; 530; Metallorganisches Netzwerk; Röntgen-Photoelektronenspektroskopie; Röntgenabsorptionsspektroskopie; LEED; Cobalt; Nickel; Kohlenmonoxid; Stickstoffdioxid